2011
DOI: 10.1103/physreva.84.033619
|View full text |Cite
|
Sign up to set email alerts
|

Quantum magnetism with polar alkali-metal dimers

Abstract: We show that dipolar interactions between ultracold polar alkali-metal dimers in optical lattices can be used to realize a highly tunable generalization of the t-J model, which we refer to as the t-J -V -W model. The model features long-range spin-spin interactions J z and J ⊥ of XXZ type, long-range density-density interaction V , and long-range density-spin interaction W , all of which can be controlled in both magnitude and sign independently of each other and of the tunneling t. The "spin" is encoded in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
262
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(263 citation statements)
references
References 117 publications
(317 reference statements)
1
262
0
Order By: Relevance
“…(1) could be experimentally realized by loading ultracold polar molecules into an optical lattice and applying an external dc electric field perpendicular to the plane of the lattice [30,31]. Two rotational states |m 0 and |m 1 of a molecule form the effective spin states |↑ and |↓ , respectively.…”
Section: The T-j-v -W Hamiltonianmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) could be experimentally realized by loading ultracold polar molecules into an optical lattice and applying an external dc electric field perpendicular to the plane of the lattice [30,31]. Two rotational states |m 0 and |m 1 of a molecule form the effective spin states |↑ and |↓ , respectively.…”
Section: The T-j-v -W Hamiltonianmentioning
confidence: 99%
“…Recently, it was shown that polar molecules in optical lattices can be used to simulate a highly tunable generalization of the t-J Hamiltonian, referred to as the t-J -V -W Hamiltonian [30,31]. The latter differs from the t-J Hamiltonian in the following aspects: it has anisotropic XXZ spin-spin interactions J ⊥ and J z , an independent density-density interaction V , a spin-density interaction W , and the interactions are long-range dipolar rather than nearest-neighbor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Powerful microwave dressing techniques borrowed from the polar-molecule literature [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] can be used to access a great variety of Hamiltonians beyond the one given in Eq. (6) …”
Section: Applications To Exotic Quantum Magnetismmentioning
confidence: 99%
“…Second, cold atoms typically interact via weak contact interactions. Spin systems with strong and long-range interactions can be achieved by admixing van der Waals interactions between Rydberg states [34,35] or by replacing atoms with dipoledipole interacting polar molecules [36][37][38]. In particular, it has been shown that the dipole-dipole interaction can give rise to topological flat bands [39,40] and fractional Chern insulators [41].…”
mentioning
confidence: 99%